Effectiveness of a structured pharmaceutical review of pharmacotherapeutic plans to reduce drug-related problems in nursing homes: a study protocol of a pragmatic quasi-experimental trial - Campabadal-Prats, Cecília; Aragonès, Enric; Romeu, Marta; Salom-Garrigues, Clara; Bejarano, Ferran; Martín Luján, Francisco; Canadell, Laura (Frontiers in Pharmacology, 2025)
BackgroundPatients living in nursing homes have increased aging, comorbidity, spending on health resources and mortality. High drug use is associated with an increased risk of falls, disability, and death. It is estimated that 20%–50% of inappropriate medications are consumed in the elderly.ObjectiveThis abstract outline the study protocol for evaluating the effectiveness of a pharmaceutical intervention designed to optimize medication use among nursing home residents, with a particular focus on reducing drug-related problems (DRPs) and minimizing polypharmacy.HypothesisThe pharmaceutical intervention led by a primary care pharmacist and based on systematically reviewing the pharmacotherapeutic plans of patients admitted to nursing homes will effectively improve the quality and safety of treatment plans.MethodologyPre-post, quasi-experimental intervention study with a control group and prospective 3-month follow-up of a cohort of patients in nursing homes. The intervention consists of a clinical review of the pharmacotherapeutic plan carried out by the pharmacist and subsequently agreed upon in the pharmacotherapeutic advisory committee.DeterminationsThe study variables will be evaluated at baseline and 3 months post-intervention. The outcome variables are drug-related problems and polymedication.Statistical analysisPercentage change will be measured before and after the intervention. Descriptive statistics will be performed for quantitative variables such as qualitative and comparison of means and proportions.Expected resultsDecreasing 10% DRPs in terms of number of DRPs per patient as well as the proportion of patients experiencing DRPs. Reducing 10% polymedication in terms of the number of drugs per patient as well as the number of polymedicated patients.Applicability and relevanceThis study will expand the collaboration between the pharmacy and primary care physicians, promoting the continuum of care, strengthening the safety culture, and improving prescribing habits.EthicsThe protocol was approved by the Research Ethics Committee of the Jordi Gol Primary Care Research Institute (IDIAP), Barcelona, 22/191-EOm.Trial registrationclinicaltrials.gov, NCT05944328 Registered.